Answer:
-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2
Step-by-step explanation:
-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2-11x-7=-3x^2
2/5 + (-4/5) = -2/5!
⭐ Please consider brainliest! ⭐
✉️ If any further questions, inbox me! ✉️
Answer:
Sorry I don't talk uwu voice I don't no wat to speak uwuuu I just yry one
Answer:
10
Step-by-step explanation:
130+40+x =180
x=10
option 2 is correct
Elijahlouis, I will not sure how I am going on with my friends. we will need the following